Development of Morotai Island-North Maluku based on oceanographic-ecosystem condition - Noir P. Purba; Heti Herawati; Lantun P. Dewanti; Ibnu Faizal; Izza M. Apriliani; Marine K. Martasuganda (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
Morotai Island is developing district located in the North of North Halmahera and one of the areas that has potential source from ecosystem biodiversity. This biodiversity is very unique related to ocean condition such as ocean currents and other properties. This research used survey data in 2015 and other data from satellite and database insitu. The results showed that the Sea Surface Temperature (SST) ranges from 26.7 0C to 32.8 0C and the salinity ranges from 33.48 to 36.8 psu characterized by open ocean. The ocean currents patterns different in surrounding area due to variety of depth, tide effect, monsoonal situation, and local aspects. The mangrove area mostly located in the south, while coral reef stands in the almost coastal area. This region is mostly influenced by monsoons and also the Indonesia throughflow. From the results, the location in the southern part is very suitable for marine culture and tourism, while in the northern region it is very suitable for tourism, conservancy, and fishing. These activities will lead Morotai as an important area for enhancing the local revenue